Preparation and Incorporation of Functional Ingredients in Edible Films and Coatings - Ribeiro, A.M. (2021)
Edible films and coatings are thin layers, with a thickness of generally less than 0.3 mm, that are used for centuries to protect food products and to avoid the deterioration of their ingredients. While an edible coating is formed directly on the food surface by spraying, dipping or spreading techniques, an edible film is first produced by solvent casting, compression moulding or extrusion procedures and posteriorly implemented into the food products, being placed on or between food components. The food sector is the main consumer of packaging materials, with the edible films and coatings being mainly applied into meat and seafood, fruits and vegetables and dairy products. These packaging materials, normally formed by a cohesive structured biopolymer, additives and/or a solvent, can also be used as carriers of several active ingredients, like colourants, flavours, nutrients and antimicrobial and antioxidant compounds, which can prolong the shelf life, improve the organoleptic characteristics and enhance the nutritional value of the final product. Nowadays, due to health and environmental concerns, the use of natural antioxidant and antimicrobial sources, like natural extracts, is emerging in the packaging research sector, being widely applied as active ingredients in edible film and coating formulations. A wide range of studies revealed the comprehensive interests in edible films and coatings with functional properties. So, the main objective of this review is to cover the recent works on edible films and coatings, including the investigation of recent advances in the incorporation of active compounds, namely natural extracts, and the challenges and opportunities for future research.